Tailoring Local Content into English for Tourism Materials: Needs of Tourism Students in Central Kalimantan - Farida, Muthia; Rizky Amelia; Handoko; Ati; Luh Maya Rani (Universitas Muhammadiyah Kalimantan Timur, 2025)
English for Tourism in tourism education institutions should equip students with English skills relevant to their academic and workplace settings. In Central Kalimantan, the tourism students must also have the knowledge of local tourism. Unfortunately, no English for Tourism book currently includes relevant local content. To address this gap, a needs analysis was conducted to explore the necessary language skills, topics, and local content to be incorporated into English for Tourism materials for these students. This research employed both quantitative and qualitative methods, utilizing a questionnaire and a focused-group interview. This research has shown a number of findings. It was revealed that the students prioritize speaking, listening and vocabulary, followed by other skills and components. They also need the materials that cover a range of topics, including general and local tourism content. Tour guiding, describing tourist spots, and tourism-related jobs were among the preferred essential topics. Last, the local content should encompass historical and cultural sites, natural tourism spots in Central Kalimantan, Dayak cultural and arts performances, Dayak traditions, as well as animal conservation and ecotourism. Tailoring local content into English for Tourism materials will better facilitate the students improving their English competence ready to fit the actual demand of the tourism sector in Central Kalimantan.